Is (poly-) substance use associated with impaired inhibitory control? A mega-analysis controlling for confounders. (October 2019) - Liu, Yang; van den Wildenberg, Wery P.M.; de Graaf, Ysanne; Ames, Susan L.; Baldacchino, Alexander; Bø, Ragnhild; Cadaveira, Fernando; Campanella, Salvatore; Christiansen, Paul; Claus, Eric D.; Colzato, Lorenza S.; Filbey, Francesca M.; et al.
Highlights: The association between polysubstance use and inhibition is as-yet-unknown. This association was tested with a mega-analysis using individual participant data. Only lifetime cannabis use was associated with suboptimal inhibition (stop-task). Lifetime cannabis use moderated tobacco's effect on response inhibition. In cannabis non-users only, tobacco use was associated with suboptimal inhibition. Abstract: Many studies have reported that heavy substance use is associated with impaired response inhibition. Studies typically focused on associations with a single substance, while polysubstance use is common. Further, most studies compared heavy users with light/non-users, though substance use occurs along a continuum. The current mega-analysis accounted for these issues by aggregating individual data from 43 studies (3610 adult participants) that used the Go/No-Go (GNG) or Stop-signal task (SST) to assess inhibition among mostly "recreational" substance users (i.e., the rate of substance use disorders was low). Main and interaction effects of substance use, demographics, and task-characteristics were entered in a linear mixed model. Contrary to many studies and reviews in the field, we found that only lifetime cannabis use was associated with impaired response inhibition in the SST. An interaction effect was also observed: the relationship between tobacco use and response inhibition (in the SST) differed between cannabis users and non-users, with a negative association between tobacco use and inhibition in the cannabis non-users. In addition, participants' age, education level, and some task characteristics influenced inhibition outcomes. Overall, we found limited support for impaired inhibition among substance users when controlling for demographics and task-characteristics.